2019
DOI: 10.11118/actaun201967061613
|View full text |Cite
|
Sign up to set email alerts
|

The Czech Agrarian Trade Comparative Advantages Distribution Based on Value and Volume Approach

Abstract: In the last two decades, the Czech agrarian trade has undergone a very significant transformation. It had been considerably influenced by several dynamically developing factors, which originate not only in the area of economics, but also within the political and social sphere. The objective of this paper is to identify the roots of Czech agrarian trade competitiveness in relation to EU and non-EU countries. The results of comparative advantages analyses are discussed in relation to Czech agrarian trade nominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Jambor [59] states that the Czech Republic, similar to the rest of the V4 countries, decreased the comparative advantage in relation to the EU-15 countries after EU accession. The bilateral comparative advantages of Czech agricultural trade with regard to individual EU partners were revealed by Smutka et al [46] for the following aggregates: CN10 (cereals), CN24 (tobacco and manufactured tobacco substitutes), CN01 (live animals; animal products), CN12 (oil seeds and oleaginous fruits; miscellaneous grains, seeds and fruit; industrial or medicinal plants; straw and fodder), CN15 (animal or vegetable fats and oils and their cleavage products; prepare edible fats; animal or vegetable waxes), CN04 (dairy produce; birds' eggs; natural honey; edible products of animal origin, not elsewhere specified or included), CN22 (beverages, spirits and vinegar), CN11 (products of the milling industry; malt; starches; inulin; wheat gluten), CN17 (sugars and sugar confectionery), CN03 (fish and crustaceans, mollusks and other aquatic invertebrates), CN16 (preparations of meat, of fish or of crustaceans, mollusks or other aquatic invertebrates), CN09 (coffee, tea, maté and spices), CN13 (lac; gums; resins and other vegetable saps and extracts) and CN14. Similarly, according to Burianová and Belová [60], the Czech agri-food trade as one category does not have a comparative advantage in relation to all trade partners, but if the analysis is focused on the individual agri-food trade components' (aggregations) competitiveness, at least some aggregations are able to get a comparative advantage in relation to the global market.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Jambor [59] states that the Czech Republic, similar to the rest of the V4 countries, decreased the comparative advantage in relation to the EU-15 countries after EU accession. The bilateral comparative advantages of Czech agricultural trade with regard to individual EU partners were revealed by Smutka et al [46] for the following aggregates: CN10 (cereals), CN24 (tobacco and manufactured tobacco substitutes), CN01 (live animals; animal products), CN12 (oil seeds and oleaginous fruits; miscellaneous grains, seeds and fruit; industrial or medicinal plants; straw and fodder), CN15 (animal or vegetable fats and oils and their cleavage products; prepare edible fats; animal or vegetable waxes), CN04 (dairy produce; birds' eggs; natural honey; edible products of animal origin, not elsewhere specified or included), CN22 (beverages, spirits and vinegar), CN11 (products of the milling industry; malt; starches; inulin; wheat gluten), CN17 (sugars and sugar confectionery), CN03 (fish and crustaceans, mollusks and other aquatic invertebrates), CN16 (preparations of meat, of fish or of crustaceans, mollusks or other aquatic invertebrates), CN09 (coffee, tea, maté and spices), CN13 (lac; gums; resins and other vegetable saps and extracts) and CN14. Similarly, according to Burianová and Belová [60], the Czech agri-food trade as one category does not have a comparative advantage in relation to all trade partners, but if the analysis is focused on the individual agri-food trade components' (aggregations) competitiveness, at least some aggregations are able to get a comparative advantage in relation to the global market.…”
Section: Discussionmentioning
confidence: 98%
“…), HS22 (beverages, spirits and vinegar), HS03 (fish and crustaceans) and HS13 (lac, gums, resins, etc.). Moreover, Smutka et al [46] found that even Czech agricultural trade does not have comparative advantages in general. Jambor [59] states that the Czech Republic, similar to the rest of the V4 countries, decreased the comparative advantage in relation to the EU-15 countries after EU accession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth emphasizing that using XUV as an indicator of the quality of goods is a simplification and has been subject to criticism (King, 1993;Silver, 2009). However, several studies have justified the legitimacy of using XUV as a quality indicator (Anwar and Sun, 2018;Smutka et al, 2019). Based on Bajan et al (2021), we recognize goods as the same quality when they fulfil the condition of the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…Hummels and Klenow, 2005; Mau 2019), or specifically in agri-food trade (e.g. Janský, 2010;Smutka et al, 2019). Hallak (2006) also claims that differences in quality are better seen between less homogeneous goods, whereas goods exhibiting uniform features differ in quality to a lower extent.…”
Section: Analysis Of Eu Us and China Marketmentioning
confidence: 99%